Inhibition of TMEM16A Ca2+-activated Cl− channels by avermectins is essential for their anticancer effects. (June 2020) - Zhang, Xuan; Zhang, Gaohua; Zhai, Wenjing; Zhao, Zhijun; Wang, Sheng; Yi, Jianfeng
Graphical abstract: Abstract: Transmembrane member 16A (TMEM16A) encoded Ca 2+ -activated Cl − channels were found to be involved in tumorigenesis. Previous studies suggest the effect of TMEM16A gene amplification on tumorigenic proliferation is exerted through its channel function. TMEM16A-specific and potent small molecule inhibitors have been proposed to potentially be useful for the treatment of cancer. Thus, we screened six analogues of avermectin for their inhibitory activities on TMEM16A mediated currents. A whole-cell patch technique was used to record the currents. The IC50 and Emax values for TMEM16A inhibition of five tested avermectins (avermectin B1, ivermectin, doramectin, selamectin, and moxidectin) were 0.15–1.32 μM and 65–87 %, respectively. In addition, these avermectins significantly inhibited endogenous TMEM16A mediated currents and thus, the proliferation, migration, inducing apoptosis of LA795 cancer cells. Eprinomectin (4"-(acetylamino)-4"-deoxy-avermectin B1 ) and two other important macrolides (erythromycin and azithromycin), which have minimal or no TMEM16A inhibitory effects, were used as negative control drugs. These drugs were found to have limited effects on the proliferation, migration, and apoptosis of LA795 cells. Finally, avermectin B1 and ivermectin dramatically inhibited the growth of xenograft tumors in mice. These data demonstrate that avermectins are novel TMEM16A inhibitors and are potentially useful in specific cancer therapies. These findings also provide a new opportunity to develop TMEM16A modulators.